2012
DOI: 10.1007/s10928-011-9235-z
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic modelling of S-warfarin to evaluate the design of drug–drug interaction studies for CYP2C9

Abstract: This study is to assess pharmacokinetic (PK) sampling time schedules and trial size requirements of drug-drug interaction (DDI) studies for CYP2C9, based on S-warfarin population PK models. S-warfarin plasma concentrations from eight DDI studies were utilized to develop S-warfarin population PK models. Optimal PK sampling times were obtained that minimized mean squared error of geometric mean of the area under the concentration-time curve (AUC(0-∞)). The powers and type I error rates of testing the equivalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…S-warfarin is metabolized by the polymorphic CYP2C9 enzyme and hence is the substrate selected to investigate the drug-drug interactions for CYP2C9 by the US Food and Drug Administration (FDA), while R-warfarin is metabolized by a combination of CYP isoforms including CYP1A2 and CYP 3A4. It has also been reported that the anticoagulant action of racemic warfarin is mostly due to the S-warfarin and to predict any drug-drug interaction requires only the monitoring of S-warfarin (Klein et al, 2012).…”
Section: Figurementioning
confidence: 99%
“…S-warfarin is metabolized by the polymorphic CYP2C9 enzyme and hence is the substrate selected to investigate the drug-drug interactions for CYP2C9 by the US Food and Drug Administration (FDA), while R-warfarin is metabolized by a combination of CYP isoforms including CYP1A2 and CYP 3A4. It has also been reported that the anticoagulant action of racemic warfarin is mostly due to the S-warfarin and to predict any drug-drug interaction requires only the monitoring of S-warfarin (Klein et al, 2012).…”
Section: Figurementioning
confidence: 99%
“…PDDIs often are between drugs that are metabolized by the same cytochrome P450 (CYP450) enzymes, and/or due to the administration of drugs that inhibit or induce these enzymes systems (Spriet et al, 2009;Klein, Gueorguieva, Aarons, 2012;Mouly, Meune, Bergmann, 2009). Drugs metabolized by this route include midazolam, tacrolimus, cyclosporine, and phenytoin, all of which are widely used in the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies used chiral high-performance liquid chromatography (HPLC) to measure the plasma concentrations of S-warfarin or S-warfarin and R-warfarin. [19][20][21][22] Klein et al 23 did not mention any bioanalysis method or sample type used to estimate warfarin concentration.…”
Section: Bioanalytical Methodsmentioning
confidence: 99%